+0  
 
0
410
1
avatar

                   36^-1/2

36^5/2   .     ----------

                 (36^-1)^-7/2

Guest Jan 13, 2015

Best Answer 

 #1
avatar+93691 
+5

$$\\36^{5/2}\times \frac{36^{-1/2}}{ (36^{-1})^{-7/2}}\\\\
=6^5\times \frac{6^{-1}}{ 36^{-1*(-7/2)}}\\\\
=6^5\times \frac{6^{-1}}{ 36^{7/2}}\\\\
=6^5\times \frac{6^{-1}}{ 6^7}\\\\
=6^{5-1-7}\\\\
=6^{-3}\\\\
=\frac{1}{6^3}\\\\
=\frac{1}{108}\\\\$$

Melody  Jan 13, 2015
 #1
avatar+93691 
+5
Best Answer

$$\\36^{5/2}\times \frac{36^{-1/2}}{ (36^{-1})^{-7/2}}\\\\
=6^5\times \frac{6^{-1}}{ 36^{-1*(-7/2)}}\\\\
=6^5\times \frac{6^{-1}}{ 36^{7/2}}\\\\
=6^5\times \frac{6^{-1}}{ 6^7}\\\\
=6^{5-1-7}\\\\
=6^{-3}\\\\
=\frac{1}{6^3}\\\\
=\frac{1}{108}\\\\$$

Melody  Jan 13, 2015

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.